Studies on electronic conductivity and structural of PVA Chi/Mg(CF3SO3)2/L-leucine solid electrolytes / Syaiful Izwan Ismail - Ismail, Syaiful Izwan (2008)
More environmental friendly and more biodegradable ionic cells are some of the properties that could give a good electrolyte. In order to obtain a maximum ionic conductivity of solid electrolyte, study of the determination of optimum composition of Mg-based solid electrolyte was completed by making thin film. In addition, the electronic conductivity and structural characteristic of the electrolyte was also carried out. Solid poly(vinylalcohol), (PVA); chitosan; magnesium trifluoromethanesulfonate, (Mg(CF3SO3)2)); and L-leucine was mixed in 1% acetic acid to form homogeneous solution. The solution was casted to a dish and was let evaporated to form thin films. The film was then characterized for determining it ionic conductivity.